The Effect of Education and Training on Employee Performance through Competency as Intervening Variable: The Case of BNI Multifinance Marketing Palembang Branch - Wuri, Hutariadi; Idris, Muhammad; Asiati, Diah Isnaini (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine the effect of education and training on employee performance, with competency serving as an intervening variable in marketing at the BNI Multifinance Palembang Branch. The object of this study is marketing employees at the BNI Multifinance Palembang Branch. The research method employed is associative research, involving two exogenous variables and two endogenous variables. The sampling technique used is proportionate stratified random sampling. The data used are primary data obtained from the results of questionnaire answers. The analysis technique employed is structural equation modeling (SEM). The results of this study indicate: (1) There is a significant effect of education on the performance of marketing employees at BNI Multifinance Palembang Branch, (2) There is a significant effect of training on the performance of marketing employees at BNI Multifinance Palembang Branch, (3) There is a significant effect of education on the competence of marketing employees at BNI Multifinance Palembang Branch, (4) There is a significant effect of training on the competence of marketing employees at BNI Multifinance Palembang Branch, and (5) There is a significant effect of competence on the performance of marketing employees at BNI Multifinance Palembang Branch